БЎЛАЖАК ПЕДАГОГ-ПСИХОЛОГЛАРНИНГ КАСБИЙ КОМПЕТЕНЦИЯНИ ОШИРУВЧИ ИЖТИМОИЙ-ПСИХОЛОГИК ФАКТОРЛАРНИНГ ОЛИМЛАР ТОМОНИДАН ЎРГАНИЛИШИ - Даукеева, А. (SCIENCE and SOCIETY, 2024)
This article studies the socio-psychological factors in the formation of educational motivation in students, the professional competence of a teacher-psychologist with knowledge in the field of pedagogy and psychology, as well as the work of a teacher on himself, the effective management of the educational process at school experience.